In vitro and in vivo assessment of magnetically actuated biomaterials for tendon regeneration - Santos, L. J. (2016)
Tendon regeneration can be undermined by the formation of fibrous adhesions (scar tissue) between the healing tendon and the surrounding tissues. Scarring is associated with the recruitment of inflammatory cells such as macrophages and mast cells[1]. To tackle this issue we advocate the implementation of postoperative rehabilitation programmes to control inflammation levels and scarring, ensuring this way better clinical outcomes. In this study we propose the insertion of a magnetic responsive biomaterial between the healing tendon and the surrounding tissues. We hypothesise this material in combination with a magnetic field will modulate inflammation and reduce fibrous adhesion. Here we present the results from the first stage of our study, where magnetic biomaterials were tested subcutaneously to evaluate the inflammatory response and the ability of this material to control the presence of fibrous tissue.